The sculptural body in Victorian literature: encrypted sexualities - Pulham, Patricia (Edinburgh critical studies in victorian culture, 2020)
This book argues that, in Victorian literature, transgressive desires that cannot be openly acknowledged are often buried and encrypted in the marble bodies of statues.